Cuidados críticos en el paciente perioperatorio - Fernando Rodriguez-Solana (Critical Care & Emergency Medicine, 2026)
Abstract: The perioperative critically ill patient represents a complex clinical challenge that begins at the first point of medical contact, whether in the prehospital or in-hospital setting. Management requires a comprehensive strategy aimed at hemodynamic, ventilatory, metabolic, and multiorgan optimization, with special emphasis on safety during transport and transition to the intensive care unit (ICU). This review describes current principles in the comprehensive management of the perioperative critically ill patient, emphasizing monitoring strategies, resuscitation, multiorgan support, and complication prevention. Current evidence supports dynamic clinical monitoring complemented by bedside ultrasonography (FATE, RUSH, and VEXUS protocols), prioritizing individualized perfusion targets. Fluid resuscitation should be physiology-driven, avoiding fluid overload and favoring balanced crystalloid solutions. Rational use of vasopressors—particularly norepinephrine—remains the cornerstone of vasoplegic management. Lung-protective ventilation, appropriate glycemic control, restrictive transfusion strategies, and early identification of acute kidney injury using emerging biomarkers contribute to improved outcomes. Early enteral nutrition, multimodal analgesia, and non-pharmacological interventions for delirium prevention are essential components of comprehensive supportive care. The management of the perioperative critically ill patient must be multidisciplinary, dynamic, and individualized, prioritizing continuous bedside clinical assessment and physiology-based decision-making supported by contemporary evidence, with the aim of reducing morbidity and mortality and improving clinical outcomes.